2002
DOI: 10.1038/sj.leu.2402497
|View full text |Cite
|
Sign up to set email alerts
|

Ear involvement in acute promyelocytic leukemia at relapse: a disease-associated ‘sanctuary’?

Abstract: Extramedullary (EM) involvement occurs infrequently in acute promyelocytic leukemia (APL) and usually involves skin and CNS. We describe seven patients (four observed at a single institution) who relapsed in various sites of the auditory apparatus, including the external canal and middle ear (temporal bone). Front-line treatment included ATRA and chemotherapy (six patients) or chemotherapy alone (one patient). Three patients had concomitant hematologic relapse, two had molecular relapse and two were in hematol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…[26][27][28] However, those presenting features may also be absent in case of ear involvement. 18 Finally, it has been suggested that occurrence of RA syndrome might be associated with an increased risk of EM relapse. 14 In our study, patients with EM relapse had significantly higher WBC counts at diagnosis, a higher incidence of bcr3 PML-RARa isoform but, also, were significantly younger than the other APL patients included in the study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[26][27][28] However, those presenting features may also be absent in case of ear involvement. 18 Finally, it has been suggested that occurrence of RA syndrome might be associated with an increased risk of EM relapse. 14 In our study, patients with EM relapse had significantly higher WBC counts at diagnosis, a higher incidence of bcr3 PML-RARa isoform but, also, were significantly younger than the other APL patients included in the study.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Although very rare in APL in the past, [9][10][11] cases of extramedullary (EM) relapse have been increasingly reported in the last few years. [12][13][14][15][16][17][18] Those EM relapses largely predominate in the central nervous system (CNS) and the skin, followed by other sites (testes, sites of vascular access, external ear and auditory canal). [12][13][14][15][16][17][18] It has been suggested that EM relapse may be associated with initial adverse prognostic features (including high WBC counts, microgranular morphology and bcr3 isoform), 12,15,17 but risk factors for EM relapse have not been precisely defined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…70 A growing body of evidence, however, shows that an extramedullary relapse of APL is frequently observed among patients who have been induced into CR by ATRA regimens, including some hitherto rare relapse sites such as the external auditory canal. [71][72][73][74][75] There are a couple of explanations why extramedullary relapse is more common in patients treated with ATRA. First, ATRA reportedly upgrades the transcription of some leukocyte adhesion molecule genes, and thus ATRA-treated leukemia cells may show increased expression of adhesion molecules.…”
Section: Extramedullary Leukemia and Its Managementmentioning
confidence: 99%
“…[3,4] Central nervous system, skin, testicle, vascular access, external ear, and auditory canal are the most common EM relapse sites. [3][4][5][6][7][8] Before the ATRA era, the large majority of first relapses in APL occurred within 3 years of complete remission, and only 2% to 3% of patients relapsed after 4 years. [9] Disclosures Peer-review: Externally peer-reviewed.…”
mentioning
confidence: 99%